2009
DOI: 10.1007/s11262-009-0344-3
|View full text |Cite
|
Sign up to set email alerts
|

HIV Tat potentiates cell toxicity in a T cell model for sulphamethoxazole-induced adverse drug reactions

Abstract: HIV infection results in severe immune dysfunction with ensuing sequelae that includes characteristic opportunistic infections. Pneumocystis pneumonia (PCP) is one of the most common of these infections and is routinely treated with sulphamethaxazole (SMX). Although this drug is known to cause hypersensitivity adverse drug reactions (ADRs) in 0.1% of the general population, the incidence of these ADRs increases tenfold in the HIV-positive population. The HIV-1 trans-activator of transcription (HIV-1 Tat) toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 48 publications
1
20
1
Order By: Relevance
“…ADRs to SMX in patients undergoing antiretroviral therapy arise increasingly as HIV-1 infection progresses to AIDS suggesting that HIV-1 is a key contributing factor. Previously, our research has shown that the HIV-1 Tat protein is such a factor as Tat expression correlates with increased sensitivity to SMX-HA, the reactive metabolite of SMX [8,21]. In this study we sought to determine the region of the Tat protein mediating this effect.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…ADRs to SMX in patients undergoing antiretroviral therapy arise increasingly as HIV-1 infection progresses to AIDS suggesting that HIV-1 is a key contributing factor. Previously, our research has shown that the HIV-1 Tat protein is such a factor as Tat expression correlates with increased sensitivity to SMX-HA, the reactive metabolite of SMX [8,21]. In this study we sought to determine the region of the Tat protein mediating this effect.…”
Section: Discussionmentioning
confidence: 98%
“…We have previously demonstrated SMX-HA induced cell death via apoptosis in a cultured T cell line expressing the first exon of the HIV-1 Tat protein [21]. Here we determine the mechanism by which SMX -HA enhances Tat's ability to promote apoptosis using the full-length form of Tat.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations